Alternative Fusion Fuels and Systems - Ryzhkov, Sergei V.; Chirkov, Alexei Yu. (Boca Raton, FL : CRC Press, 2019)
Explores the systems of magnetic confinement of high-temperature plasma with closed and open magnetic field lines which relate to alternative compact devices of controlled thermonuclear fusion. Energy balance schemes of thermonuclear plasmas and main reactor characteristics are presented as the authors compare conceptual projects based on classical tokamak and stellarator, spherical tokamak and compact torus. They explore the questions and problems of new promising nuclear and thermonuclear power plants that source thermonuclear neutrons on a mixture of deuterium and tritium, and a low-radioactive reactor on a mixture of deuterium and helium-3.
OCLC-licensed vendor bibliographic record.
Keywords: Nuclear fusion; Nuclear fuel elements; Synthetic fuels; SCIENCE / Physics / Quantum Theory; SCIENCE / Energy; SCIENCE / Nuclear Physics; SCIENCE / Physics